Olfactory Dysfunction in Familial and Sporadic Parkinson's Disease - Chase, Bruce A.; Markopoulou, Katerina (Frontiers in Neurology, 2020)
This minireview discusses our current understanding of the olfactory dysfunction that is frequently observed in sporadic and familial forms of Parkinson’s disease and parkinsonian syndromes. We review the salient characteristics of olfactory dysfunction in these conditions, discussing its prevalence and characteristics in sporadic and familial Parkinson’s disease, the contributions of neuronal processes and circuits and how they are altered in Parkinson’s disease, and what clinically used measures of olfactory function assess. We highlight how studies of monogenic Parkinson’s disease and investigations in ethnically diverse populations have contributed to understanding the underlying mechanisms of olfactory dysfunction. Furthermore, we discuss how imaging and system-level approaches have been used to understand the pathogenesis of olfactory dysfunction. We discuss the challenging, remaining gaps in understanding the basis of olfactory dysfunction in neurodegeneration and how insights could be obtained by following longitudinal cohorts with familial forms of Parkinson’s disease using a combination of approaches. We argue that a multifaceted longitudinal assessment of olfactory function during disease progression is essential to identify the not only how dysfunction arises, but also to address its relationship to motor and non-motor Parkinson’s disease symptoms. A multifaceted longitudinal assessment of monogenic cohorts with familial PD available within the GEoPD and other consortia will have heuristic value in addressing the complexity of olfactory dysfunction during the neurodegenerative process. This will inform our understanding of Parkinson’s disease as a multisystem disorder and facilitate the more effective use of olfactory dysfunction in identifying prodromal Parkinson’s disease and understanding disease progression.